The Ubiquitin Ligase CBLC Maintains the Network Organization of the Golgi Apparatus - Lee, Wan Yin (PLoS One, 2015)
The Golgi apparatus plays a pivotal role in the sorting and post-translational modifications of secreted and membrane proteins. In mammalian cells, the Golgi is organized in stacks of cisternae linked together to form a network with a ribbon shape. Regulation of Golgi ribbon formation is poorly understood. Here we find in an image-based RNAi screen that depletion of the ubiquitin-ligase CBLC induces Golgi fragmentation. Depletions of the close homologues CBL and CBLB do not induce any visible defects. In CBLC-depleted cells, Golgi stacks appear relatively unperturbed at both the light and electron microscopy levels, suggesting that CBLC controls mostly network organization. CBLC partially localizes on Golgi membranes and this localization is enhanced after activation of the SRC kinase. Inhibition of SRC reverts CBLC depletion effects, suggesting interplay between the two. CBLC’s regulation of Golgi network requires its ubiquitin ligase activity. However, SRC levels are not significantly affected by CBLC, and CBLC knockdown does not phenocopy SRC activation, suggesting that CBLC’s action at the Golgi is not direct downregulation of SRC. Altogether, our results demonstrate a role of CBLC in regulating Golgi ribbon by antagonizing the SRC tyrosine kinase.